Pertumbuhan Kinerja Bisnis Transportasi Bus Umum Antar Kota Antar Provinsi - John Sihotang; R.A. Aryanti Wardaya Puspokusumo; Prapto Utomo (Institut Transportasi dan Logistik Trisakti, 2019)
For the past five years, the business performance of intercity and interprovincial bus company (AKAP) was fluctuated. Even in the last two years, the trend was decreasing due to the increasing number of bus passengers who were switching to other modes of transportation. The customer satisfaction index (CSI) score of Bus as public transportation is the lowest compared to CSI of other public transport such as train, and airplane. This study aims at examining the impact of service quality on growth of AKAP public bus company’s business performance in West Java. The research method used was a quantitative method using a survey questionnaire of 80 companies in the province of West Java. The results show that service orientation has a significant impact on the AKAP's business performance growth. Further analysis shows that both reliability and responsiveness are the main factors in building service quality orientation. Thus, the AKAP bus managers need to focus more on competing with other transportation mode. The role of the government is also needed to develop the AKAP bus managers’capability in order to build an efficient transportation system.